(untitled) (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the scientific journal "Ágora de Heterodoxias" (ISSN: 2443-4361) of the Universidad Centroccidental Lisandro Alvarado, Venezuela. This means of scientific dissemination was created in 2015, as a multidisciplinary journal, attached to the Dean of Economic and Business Sciences of said university, published biannually, with the purpose of contributing to the dissemination of scientific works by national and international researchers. As of 2018, it publishes articles in Social Sciences.